A Clinical Classification of the Acute Respiratory Distress Syndrome for Predicting Outcome and Guiding Medical Therapy*. Issue 2 (February 2015) - Villar, Jesús; Fernández, Rosa L.; Ambrós, Alfonso; Parra, Laura; Blanco, Jesús; Domínguez-Berrot, Ana M.; Gutiérrez, José M.; Blanch, Lluís; Añón, José M.; Martín, Carmen; Prieto, Francisca; Collado, Javier; et al.
Abstract : Objective: Current in-hospital mortality of the acute respiratory distress syndrome (ARDS) is above 40%. ARDS outcome depends on the lung injury severity within the first 24 hours of ARDS onset. We investigated whether two widely accepted cutoff values of PaO2 /FIO2 and positive end-expiratory pressure (PEEP) would identify subsets of patients with ARDS for predicting outcome and guiding therapy. Design: A 16-month (September 2008 to January 2010) prospective, multicenter, observational study. Setting: Seventeen multidisciplinary ICUs in Spain. Patients: We studied 300 consecutive, mechanically ventilated patients meeting American-European Consensus Conference criteria for ARDS (PaO2 /FIO2 ⩽ 200 mm Hg) on PEEP greater than or equal to 5 cm H2 O, and followed up until hospital discharge. Interventions: None. Measurements and Main Results: Based on threshold values for PaO2 /FIO2 (150 mm Hg) and PEEP (10 cm H2 O) at ARDS onset and at 24 hours, we assigned patients to four categories: group I (PaO2 /FIO2 ≥ 150 on PEEP < 10), group II (PaO2 /FIO2 ≥ 150 on PEEP ≥ 10), group III (PaO2 /FIO2 < 150 on PEEP < 10), and group IV (PaO2 /FIO2 < 150 on PEEP ≥ 10). The primary outcome was all-cause in-hospital mortality. Overall hospital mortality was 46.3%. Although at study entry, patients with PaO2 /FIO2 less than 150 had a higher mortality than patients with a PaO2 /FIO2 greater than or equal to 150 ( p = 0.044), there was minimal variability in mortality among the four groups ( p = 0.186). However, classification of patients in each group changed markedly after 24 hours of usual care. Group categorization at 24 hours provided a strong association with in-hospital mortality ( p < 0.00001): group I had the lowest mortality (23.1%), whereas group IV had the highest mortality (60.3%). Conclusions: The degree of lung dysfunction established by a PaO2 /FIO2 of 150 mm Hg and a PEEP of 10 cm H2 O demonstrated that ARDS is not a homogeneous disorder. Rather, it is a series of four subsets that should be considered for enrollment in clinical trials and for guiding therapy. A major contribution of our study is the distinction between survival after 24 hours of care versus survival at the time of ARDS onset.